Answer:
see explanation
Explanation:
To factorise the quadratic
Consider the factors of the product of the x² term and the constant term which sum to give the x- term
product = 6 × - 4 = - 24 and sum = - 5
The factors are + 3 and - 8
Use these factors to split the x- term
6x² + 3x - 8x - 4 = 0 ( factor the first/second and third/fourth terms )
3x(2x + 1) - 4(2x + 1) = 0 ← factor out (2x + 1)
(2x + 1)(3x - 4) = 0
Equate each factor to zero and solve for x
2x + 1 = 0 ⇒ 2x = - 1 ⇒ x = -
![(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ybjkeso7qr5r7js5h0mv9de35dih0sxfpl.png)
3x - 4 = 0 ⇒ 3x = 4 ⇒ x =
![(4)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/njuue06kwccysinu3fvpfi1udnx59yqvei.png)
Solutions are x = -
, x =
![(4)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/njuue06kwccysinu3fvpfi1udnx59yqvei.png)